Molecular organization relationship of low-bandgap polymers at the air-water interface and in solid films - Rodrigues de Oliveira, Vinicius Jessé [UNESP]; Assunção da Silva, Edilene [UNESP]; Braunger, Maria Luisa; Awada, Hussein; de Santana, Henrique; Hiorns, Roger C.; Lartigau-Dagron, Christine; de Almeida Olivati, Clarissa [UNESP] (Elsevier, 2018)
Low-bandgap organic polymers, poly[(4,4‑bis(2‑ethylhexyl)cyclopenta‑[2,1‑b:3,4‑b′]dithiophene)2,6‑diyl‑al‑(2,1,3‑benzothiadiazole)‑4,7‑diyl](PCPDTBT), and poly [(4,4′‑dioctyldithieno[3,2‑b:2′,3′d]silol‑2,6‑diyl)‑alt‑(2,1,3‑benzothiadiazole)‑4,7‑diyl)], (Si-PCPDTBT) were analyzed at the air-water interface forming a Langmuir monolayer. In order to form stable monolayers and to transfer to solid supports, amphiphilic molecules of stearic acid (SA) were mixed with them. For the pristine polymers, the floating monolayers were transferred onto solid substrates via the Langmuir-Schaefer (LS) technique. Surface pressure-area isotherms and compressibility modulus curves demonstrated that the SA incorporation to the polymers at the air-water interface modified the rheological properties of the Langmuir films, since the films became less compressible at higher pressures and there is clear conformational reorganization taking place at intermediary pressures. The UV–Vis absorption also depicted the changes on the overall film morphology by the shift on the maximum absorption bands, and along with cyclic voltammetry curves the absorption spectra made it possible to estimate the energy diagrams for the polymers. Photoconductivity effects were observed for all the sample, among which the pristine polymers fabricated by LS showed better results, suggesting that the organization provided by the Langmuir-Blodgett (LB) technique was not enough to overcome the insulating characteristic of the SA molecules in this specific configuration.
Keywords: Energy diagram; Langmuir films; Low-bandgap polymers; Photoconductivity effect; Solid thin films